Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity

Oxidative coupling of methane over La-promoted CaO catalysts: influence of precursors and catalyst preparation method - Rane, Vilas H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2010)
The oxidative coupling of methane to C(2) hydrocarbons has been studied over a series of La-promoted CaO (La/Ca = 0.05) catalysts, prepared using different precursor salts for CaO and La(2)O(3) (viz. acetates, carbonates, nitrates and hydroxides) and catalyst preparation methods (viz. physical mixing of precursors, co-precipitation using ammonium carbonate/sodium carbonate as a precipitating agent), under different reaction conditions (temperature: 700-850 degrees C, CH(4)/O(2) ratio: 4.0 and 8.0, and GHSV: 51360 cm(3).g(-1).h(-1)). The surface area and surface basicity/base strength distribution of the catalysts have also been investigated. The surface properties and catalytic activity/selectivity of the La-promoted CaO catalysts vary from catalyst to catalyst depending on the catalyst precursors used and catalyst preparation method. The basicity/base strength distribution is strongly influenced by the precursors (for CaO and La(2)O(3)) and catalyst preparation method. Basicity (total and strong basic sites measured in terms of CO(2) chemisorbed at 50 degrees C and 500 degrees C, respectively) observed for the catalyst prepared by co-precipitation method is higher than that of the catalysts prepared by physical mixing method. The catalysts prepared by the nitrates of La- and Ca- and co-precipitated by the solution of sodium carbonate and ammonium carbonate exhibit different catalytic performance in OCM. The finding that no direct relationship between the surface basicity and catalytic activity/selectivity in OCM exists indicates that basicity is not solely responsible for obtaining high selectivity to C(2) hydrocarbons.
Keywords: basicity distribution; La-promoted CaO catalysts; oxidative coupling of methane

Synthesis of acrolein by gas-phase dehydration of glycerol over silica supported bronsted acidic ionic liquid catalysts - Munshi, Mudassir K.; Lomate, Samadhan T.; Deshpande, Raj Madhukar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein. RESULTS: Dehydration of glycerol to acrolein was performed over several silica supported Bronsted acidic ionic liquids as catalysts. All the catalysts prepared were active for the synthesis of acrolein (conversion of glycerol was observed in the range 35-90% with selectivity to acrolein in the range 29-58%). CONCLUSIONS: Catalyst prepared from triphenyl (3-sulfopropyl) phosphonium 4-methylbenzenesulfonate gave good activity and selectivity at 4 h reaction time. The conversion of glycerol decreased with increase in glycerol concentration. Higher temperature (325 degrees C) resulted in significantly lower conversion as well as selectivity to acrolein. With the use of two additional traps cooled to -7 degrees C, the selectivity to acrolein increased significantly for good catalysts. (C) 2010 Society of Chemical Industry
Keywords: acidic ionic liquids; acrolein; glycerol dehydration; supported catalyst

Ecofriendly hydrogen production from abundant hydrogen sulfide using solar light-driven hierarchical nanostructured ZnIn2S4 photocatalyst - Chaudhari, Nilima S.; Bhirud, Ashwini P.; Sonawane, Ravindra S.; Nikam, Latesh K.; Warule, Sambhaji S.; Rane, Vilas H.; Kale, Bharat B. (Green Chemistry, 2011)
It is quite well-known that refineries are producing huge amount of H2S which has been used to produce sulphur and water using the well-known Claus process. This process is not an economically viable process, due to the high-cost chemical process and creates further acute environmental problems. Therefore, we have demonstrated the conversion of poisonous H2S into H-2 using an ecofriendly phocatalysis process which is a green unconventional energy source. We have investigated ecofriendly nanostructured ZnIn2S4 photocatalyst to produce hydrogen from H2S using solar light. We also demonstrate the controlled synthesis of hierarchical nanostructured ZnIn2S4 using a facile hydrothermal method. The morphologies obtained have been greatly influenced by the presence of triethylamine (TEA) with various concentrations during the reaction. Surprisingly, a highly crystalline hexagonal layer structured ZnIn2S4 was obtained instead of cubic spinel. The hierarchical nanostructure, i.e. marigold flower-like morphology, was obtained without any surfactant. The thin and transparent petals self-assembled to form the unique nanostructured marigold flower. The highly crystalline puffy marigold flowers and nanoplates/nanostrips were obtained using TEA-assisted hydrothermal synthesis. Optical study shows the band gap in the range of 2.34-2.48 eV. Considering the band gap in the visible region, ZnIn2S4 is used as photocatalyst for hydrogen production from hydrogen sulphide under solar light which is hitherto unattempted. The constant photocatalytic activity of hydrogen evolution, i.e. 5287 mu mol h(-1), was obtained using such hierarchical nanostructured ZnIn2S4 under visible light irradiation. It is noteworthy that the H-2 evolution rate obtained is much higher compared to earlier reported photocatalysts. Considering the significance of morphologies for photocatalytic application, the formation mechanism has also been furnished. The unique hierarchical nanostructured ZnIn2S4 ternary semiconductor having hexagonal layer will have potential applications in solar cells, LEDs, charge storage, electrochemical recording, thermoelectricity and other prospective electronic and optical devices.

Novel solar light driven photocatalyst, zinc indium vanadate for photodegradation of aqueous phenol - Mahapure, Sonali A.; Rane, Vilas H.; Ambekar, Jalindar D.; Nikam, Latesh K.; Marimuthu, R.; Kulkarni, Milind V.; Kale, Bharat B. (Materials Research Bulletin, 2011)
In the present investigation, we have demonstrated the synthesis of novel photocatalyst, zinc indium vanadate (ZIV) by solid solid state route using respective oxides of zinc, indium and vanadium. This novel photocatalyst was characterized using XRD, FESEM, UV-DRS and FTIR in order to investigate its structural, morphological and optical properties. XRD clearly shows the formation of phase pure ZIV of triclinic crystal structure with good crystallinity. FESEM micrographs showed the clustered morphology having particle size between 0.5 and 1 mu m. Since, optical study showed the band gap around 2.8 eV, i.e. in visible region, we have performed the photocatalytic activity of phenol degradation under visible light irradiation. The photodecomposition of phenol by ZIV is studied for the first time and an excellent photocatalytic activity was obtained using this novel photocatalyst. Considering the band gap of zinc indium vanadate in visible region, it will also be the potential candidate for water splitting. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Chemical synthesis; Oxides; X-ray diffraction

Synthesis of glycidol from glycerol and dimethyl carbonate using ionic liquid as a catalyst - Gade, Swapna M.; Munshi, Mudassir K.; Chherawalla, Batul M.; Rane, Vilas H.; Kelkar, Ashutosh A. (Catalysis Communications, 2012)
Transesterification of dimethyl carbonate with glycerol has been investigated using various ionic liquids as catalysts. Synthesis of glycidol with high selectivity (78%) has been achieved using tetramethylammonium hydroxide ([TMA][OH]) as a catalyst at 80 degrees C. Effect of various reaction conditions on the activity and selectivity was investigated and catalyst concentration had a significant influence on conversion as well as selectivity to glycidol. Activity as well as selectivity of the catalyst decreased significantly with increase in moisture content. Recycle experiment indicated slight drop in glycerol conversion and selectivity to glycidol because of dilution of reaction mixture and also the presence of products from the initial experiment. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Glycerol carbonate; Glycidol; Ionic liquid; Transesterification of glycerol

1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU): a highly efficient catalyst in glycerol carbonate synthesis - Munshi, Mudassir K.; Gade, Swapna M.; Mane, Manoj V.; Mishra, Deepti; Pal, Sourav; Vanka, Kumar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Molecular Catalysis A-Chemical, 2014)
Transesterification of dimethyl carbonate (DMC) with glycerol (GLY) was investigated using various amines as catalysts. Amidines like 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) were found to be the best catalysts for this reaction. Best results: 98% conversion of GLY with 96% selectivity to GC (TON: 9408), were obtained with DBU as a catalyst. Effect of various reaction conditions on activity and selectivity were investigated using DBU as catalyst. The mechanism of the reaction was investigated with the help of H-1, C-13 and N-15 NMR analysis and OFT calculations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DBU; Glycerol; Glycerol carbonate; transesterification

Efficient synthesis of glycerol carbonate/glycidol using 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) based ionic liquids as catalyst - Munshi, Mudassir K.; Biradar, Pradeep S.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol to glycerol carbonate has been catalyzed efficiently using basic ionic liquids as catalysts. Activity of all the ILs tested is very high and the best result (96% conversion with 82% selectivity to glycerol carbonate and 18% selectivity to glycidol) was obtained using IL1 as catalyst. The effect of catalyst loading has significant influence on the selectivity pattern. The higher activity of the ionic liquid is explained with a plausible mechanism based on the co-operative effect of both cation and anion.

Role of cation-anion cooperation in the selective synthesis of glycidol from glycerol using DABCO-DMC ionic liquid as catalyst - Munshi, Mudassir K.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol has been investigated using 1,4-diazabicyclo [2.2.2] octane (DABCO) based ionic liquid as a catalyst. DABCO reacted with dimethyl carbonate to form ionic liquid as the reaction progressed. Though the basicity of DABCO based ionic liquid was lower than that of DABCO, the catalytic activity and selectivity to glycidol was higher with DABCO based ionic liquid as a catalyst, indicating that basicity may not be the only criterion in deciding activity and selectivity of the reaction. The cooperative effect of the cation and anion of the ionic liquid is responsible for the observed results. The best results (97% glycerol conversion with 83% selectivity to glycidol and 17% selectivity to glycerol carbonate) were obtained using DABCO based ionic liquid as a catalyst. A plausible mechanism involving the role of both the cation and anion of the ionic liquid has been proposed.